At work and play: Business events as entrepreneurial spaces. (May 2018) - Crowther, Phil; Orefice, Chiara; Beard, Colin
There is inadequate literature examining, and illustrating, the integration of play and business events and how this facilitates entrepreneurial opportunities. Business events are distinct from the patterns of ordinary life and increasingly offer participants an 'invitation to play', encouraging socialization and trust. This article examines the role of play in the design of business events and how this can enable entrepreneurial outcomes. Through examination of diverse, but related, literature and three contrasting, empirically based, case studies, this article illustrates how event creators take an increasingly entrepreneurial approach. These cases range from a charity event with participants sleeping with the homeless on a city's streets, a major flooring manufacturer designing events to outsource innovation and an imaginative event activity termed 'coffee and papers'. Designing events that fuse, rather than polarize, play and work enables business event settings, and activities, which trigger entrepreneurial outcomes. This article adds to the embryonic literature and concludes by identifying four principles that underlie the effectual facilitation of play in a business event setting.